Training vs. competition in sport: State anxiety and response of stress hormones in young swimmers - Carrasco Páez, L.; Martínez-Díaz, I. C. (Journal of Human Kinetics, 2021)
This study was aimed to assess the neuroendocrine response to stress induced by different sports environments (a regular training session and a competitive event), to define the contribution of psychological and physical stress, and to check the possible relationship between state-anxiety and stress hormones responses to competitive and non- competitive sports practices. Twelve young national-level male swimmers participated in this investigation. Endorphins, adrenocorticotropin, and prolactin plasma levels were measured at baseline conditions (t0), before a regular swimming training session (t1), and before and after real swimming competition consisting of 100 m freestyle (t2 and t3, respectively). Moreover, state-anxiety was evaluated in all assessment time-points. The results showed no differences in endorphin, adrenocorticotropin, prolactin an d state-anxiety between t0 and t1; however, significant increases in endorphins (142%), prolactin (137%) and state-anxiety (13%) were observed in t2. Huge stress response was observed in t3 (increases of 35 4%, 387%, and 250% for endorphins, adrenocorticotropin, and prolactin, respectively) although state-anxiety decreased slightly. Lastly, a lack of the relationship between stress hormones and state-anxiety was found in all conditions. Mental and especially physical stress associated with sports competition induces a significant release of stress hormones which is not relevant for the regular training session.